ANALYSIS OF THE ABILITY OF CONCEPTUAL UNDERSTANDING AND MATHEMATICAL CONFIDENCE IN SOLVING PROBLEMS ON INTEGER OPERATIONS IN JUNIOR HIGH SCHOOL: West Kalimantan, Indonesia - Dwi Karsono; Jamilah Jamilah; Sandie Sandie (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to investigate the relationship between conceptual understanding and mathematical confidence in junior high school students in solving problems related to integer operations. This study involved 37 students who were measured using a quantitative approach through a descriptive correlational design. The instruments used included a test to measure conceptual understanding and a questionnaire to assess mathematical confidence. The results showed that most students had an adequate understanding of integer operations, although there were differences in their levels of mathematical confidence. Approximately 24% of students showed a very good understanding, while the other 32% obtained a good understanding. Correlation analysis showed a significant positive relationship between mathematical confidence and conceptual understanding, with a coefficient of r = 0.65, indicating that the higher the students' mathematical confidence, the better their understanding of integer concepts. Interviews with students also revealed that high levels of self-confidence encouraged them to be more active and confident in solving mathematical problems. Based on these findings, this study suggests that the development of students' mathematical confidence should be a primary focus in mathematics learning, through the implementation of problem-based learning methods and the provision of constructive feedback from teachers. Keywords: Conceptual understanding, Mathematical beliefs, integer operations, junior high school students, correlation.